Effect of processing on the antinutrient and protein contents of cassava leaves from selected varieties - Tambalo, Fides Marciana Z.; Capuno, Rosa Buena A.; Estrellana, Cyrene D.; Garcia, Jayson F.; Arcillas, Lizette Sahar N. (2023)
Cassava leaves, which are usually discarded in the cassava industry, contain high levels of protein and nutrients. However, their ue is limited by toxic cyanogens and antinutritional tannins. In the Philippines, cassava farmers have limited knowledge of the nutritional quality of the leaves. Thus, this study aimed to evaluate various processing technique to address the safety of cassava leaves intended for human and animal consumption. The three local varieties studied were Binulak, Lakan and Sultan 6. Preliminary analysis of leaves based on position determined that any leaf group could be processed since the hydrogen cyanide (HCN), tannic acid, and protein contents were not significantly different. Whole cassava leaves were subjected to processing, which resulted in lowering of total HCN ( in % mean reduction): oven-dying (55.99 %)> juicing ((17.17%), and pounding (7.58%). A combination of leaf shredding and oven-drying resulted in a reduction of HCN to safe levels except for Sultan 6. Tannic acid was also reduced significantly, whereas the change in protein content is not statistically significant. The results of the study can pave the way for the safe utilization of cassava leaves as an alternative protein and nutrient sources for humans and animals.
Keywords: Proteins; Cassava; Cyanides